Implementation Of E-Parking Management Policy In Braga Area Of Bandung City - Fatmawati Fatmawati; Yati Mulyati; Rusliadi Rusliadi; Asri Nur Aina (Program Pascasarjana Universitas Negeri Makassar, 2023)
The purpose of this study is to analyse the implementation of the Regional Regulation Policy on Parking Management in the Braga area of Bandung city. This research is based on the fact that there are often parking arrangements that interfere with traffic flow so the functions and responsibilities of the government to overcome parking problems are questioned. The type of research in this study is descriptive qualitative, while the data is collected from interviews, observation, and documentation. The data was then analysed using the Nvivo 12 Plus application. The results showed that the implementation of public parking management policies in the braga area of Bandung City has not been fully implemented because there are still violations committed by parking officers in the field. In serving the public in and out of vehicles in the parking lot has not been implemented properly, and many people do not fully understand the parking machine because the parking limit that should be used is sometimes there and sometimes not. Arranging parked vehicles so as not to interfere with traffic flow, is still not implemented because officers in the field are still parking officers who arrange vehicles on the edge of public roads exceeding one shap / one shap, the parked community is well implemented. The use of evidence (carcis) that has been corporatized by the Department of Transportation, Financial Management and Assets parking officers in using evidence (carcis) has not been implemented optimally because there are still parking officers who are dishonest and lack of socialising the e-parking policy to the community which results in a decrease in parking fees and illegal parking which makes illegal parking more and more.